Diagnostic accuracy of the BioFire® FilmArray® pneumonia panel in COVID-19 patients with ventilator-associated pneumonia - Gabriel Cojuc-Konigsberg; Alberto Moscona-Nissan; Alberto Guijosa; Christian D. Mireles Dávalos; María E. Jiménez Martínez; Mario A. Mújica Sánchez; Víctor F. Hernández Huizar; Martha A. Durán Barrón; Karen Villarreal Gómez; Regina Andrade-Galindo; Montserrat Ordóñez-Oviedo; Grecia Deloya Brito; et al. (BMC Infectious Diseases, 2023)
Abstract Background Ventilator-Associated pneumonia (VAP) is one of the leading causes of morbidity and mortality in critically ill COVID-19 patients in lower-and-middle-income settings, where timely access to emergency care and accurate diagnostic testing is not widely available. Therefore, rapid microbiological diagnosis is essential to improve effective therapy delivery to affected individuals, preventing adverse outcomes and reducing antimicrobial resistance. Methods We conducted a cross-sectional study of patients with suspected VAP and COVID-19, evaluating the diagnostic performance of the BioFire® FilmArray® Pneumonia Panel (FA-PP). Respiratory secretion samples underwent standard microbiological culture and FA-PP assays, and the results were compared. Results We included 252 samples. The traditional culture method detected 141 microorganisms, and FA-PP detected 277, resulting in a sensitivity of 95% and specificity of 60%, with a positive predictive value of 68% and negative predictive value of 93%. In samples with high levels of genetic material (> 10^5 copies/mL), the panel had a sensitivity of 94% and specificity of 86%. In addition, 40% of the culture-negative samples had positive FA-PP® results, of which 35% had > 10^5 copies/mL of genetic material. The most prevalent bacteria were Gram-negative bacilli, followed by Gram-positive cocci. The panel identified 98 genes associated with antimicrobial resistance, predominantly extended-spectrum beta-lactamases (28%). Conclusion The FA-PP is a sensitive assay for identifying bacteria causing VAP in patients with COVID-19, with a greater capacity to detect bacteria than the conventional method. The timely microbiological recognition offered by this panel could lead to optimized decision-making processes, earlier tailored treatment initiation, and improved antibiotic stewardship practices.